From Esters to Ketones via a Photoredox‐Assisted Reductive Acyl Cross‐Coupling Strategy. (2nd December 2021) - Xi, Xiaoxiang; Luo, Yixin; Li, Weirong; Xu, Minghao; Zhao, Hongping; Chen, Yukun; Zheng, Songlin; Qi, Xiaotian; Yuan, Weiming
Abstract: A method was developed for ketone synthesis via a photoredox‐assisted reductive acyl cross‐coupling (PARAC) using a nickel/photoredox dual‐catalyzed cross‐electrophile coupling of two different carboxylic acid esters. A variety of aryl, 1°, 2°, 3°‐alkyl 2‐pyridyl esters can act as acyl electrophiles while N ‐(acyloxy)phthalimides (NHPI esters) act as 1°, 2°, 3°‐radical precursors. Our PARAC strategy provides an alternative and reliable way to synthesize various sterically congested 3°‐3°, 3°‐2°, and aryl‐3° ketones under mild and highly unified conditions, which have been otherwise difficult to access. The combined experimental and computational studies identified a Ni 0 /Ni I /Ni III pathway for ketone formation. Abstract : A photoredox‐assisted reductive acyl cross‐coupling reaction of two different carboxylic acid esters was developed for ketone synthesis. The reaction proceeded smoothly under mild conditions using Hantzsch ester (HE) as an organic reductant, with high chemoselectivity and functional group compatibility. A large range of aryl and 1°, 2°, 3°‐acyl electrophiles, and 1°, 2°, 3°‐alkyl radical precursors were tolerated.